A Study of Relationships between Wetlands and Topographic Position in the Ten Soil Regions of Wisconsin - Renzoni, Dante A. (University of Wisconsin-Stevens Point, College of Natural Resources, 1980)
Through the use of topographic maps, soil survey reports, and glacial deposit maps, as well as on-site observations, the ten major soil regions, as suggested by F. D. Hole, were investigated to determine the relationship between surface landforms, glacial deposits, and the occurrence of wetlands. Using the data and examples offered in this work, anyone can learn the method needed to make reasonable predictions about soil drainage conditions anywhere in the state. These predictions would be just as accurate during abnormally dry years.